Prevalence of self-perceived audiovestibular symptoms in Egyptian COVID-19 patients - Mirhan Eldeeb; Dalia Eldeeb; Mayada Elsherif (SpringerOpen, 2023)
Abstract Background According to National Institute for Health and Care Excellence (NICE), UK, common audiovestibular symptoms of COVID-19 include dizziness, tinnitus, and otalgia. The pathogenesis of otologic disorders ranges from direct damage to the inner ear structures to immune-mediated damage. Since the start of the pandemic, the prevalence of audiovestibular symptoms linked to COVID-19 has not been thoroughly investigated in Egypt. Our objective is to study and analyze the prevalence of the audiovestibular symptoms in the Egyptian population with history of COVID-19 infection. Methods A cross-sectional study was conducted among Egyptian adults on the presence and nature of the audiovestibular manifestations in COVID-19 patients. An online questionnaire was used. The questionnaire was developed using Google Form. It was disseminated to the target population through social platforms from October 2021 till February 2022. Results Data from 245 respondents were collected through online assessment of a convenient sample. The following de novo audiovestibular symptoms were experienced by the participants: Vertigo 20.8%, hearing loss 13.9%, tinnitus 12.7% and ear fullness 11.4%. No correlation was found between the investigations done (D-Dimer, CT chest) and the audiovestibular symptoms. Conclusion Audiovestibular symptoms are fairly common among COVID-19 patients, with higher prevalence, particularly of vertigo, in our study sample compared to the literature. It is recommended that patients with audiovestibular symptoms undergo early testing so that prompt interventions can be taken.